Truncated Solutions of Painlevé Equation Pv - Costin, R.D. (Symmetry, Integrability and Geometry: Methods and Applications, 2018)
We obtain convergent representations (as Borel summed transseries) for the five one-parameter families of truncated solutions of the fifth Painlevé equation with nonzero parameters, valid in half planes, for large independent variable. We also find the position of the first array of poles, bordering the region of analyticity. For a special value of this parameter, they represent tri-truncated solutions, analytic in almost the full complex plane, for a large independent variable. A brief historical note and references on truncated solutions of the other Painlevé equations are also included.